Report on advances for pediatricians in 2018: allergy, cardiology, critical care, endocrinology, hereditary metabolic diseases, gastroenterology, infectious diseases, neonatology, nutrition, respiratory tract disorders and surgery - Carlo Caffarelli; Francesca Santamaria; Carla Mastrorilli; Angelica Santoro; Brunella Iovane; Maddalena Petraroli; Valeria Gaeta; Rosita Di Pinto; Melissa Borrelli; Sergio Bernasconi; Giovanni Corsello (BMC, 2019)
Abstract This review reported notable advances in pediatrics that have been published in 2018. We have highlighted progresses in allergy, cardiology, critical care, endocrinology, hereditary metabolic diseases, gastroenterology, infectious diseases, neonatology, nutrition, respiratory tract disorders and surgery. Many studies have informed on epidemiologic observations. Promising outcomes in prevention, diagnosis and treatment have been reported. We think that advances realized in 2018 can now be utilized to ameliorate patient care.